High HIV prevalence among injecting drug users in Estonia: implications for understanding the risk environment. - Platt, Lucy; Bobrova, Natalia; Rhodes, Tim; Uusküla, Anneli; Parry, John V; Rüütel, Kristi; Talu, Ave; Abel, Katri; Rajaleid, Kristiina; Judd, Ali (AIDS (London, England), 2006)
We found a high prevalence of HIV among injecting drug users (IDU) 54% in Tallinn and 90% in Kohtla Jarve, Estonia. Risk factors for HIV in Tallinn included use of the drug 'china white', being registered as an IDU at a drug treatment clinic, and sharing injecting equipment with sex partners. Differences existed in risk behaviour between the cities. An urgent scale-up of HIV prevention is needed. It is also important to explore how local 'risk environments' mediate the risk of HIV transmission.
Keywords: Adult; Cross-Sectional Studies; Estonia; Female; HIV Infections; Humans; Male; Prevalence; Risk Factors; Risk-Taking; Substance Abuse, Intravenous